Bilişim Sektöründeki Gelişmelerin İç ve Dış Kaynaklı İstihdam Stratejileri Üzerine Etkileri - (:unkn) unknown (My University, 2004)
Günümüzde bilişim teknolojileri hızla gelişmektedir. Kurumlar da bu teknolojik ilerlemeler dolayısıyla işçi işveren ilişkilerini yeniden düzenleme yoluna gitmektedir. Yeni teknolojilerin kuruma girmesiyle oluşan bilgi eksikliği ve bunu karşılamadaki masraflar, personelin verimsiz çalışması, çalışma süreleri, yasal ayrıntılar, sosyal güvenlik, hükümet politikaları belli başlı sorunlar oluşturmaktadır. Bu yüzden kurumlar, çeşitli iç ve dış kaynaklı istihdam stratejileri üzerinde çalışmaktadır. Kurumların çoğu bu hızlı gelişim karşısında bilişim hizmeti sağlayan personelin bir bölümünü içeriden sağlarken bir bölümünü de dışarıdan sağlamayı yeğlemektedir. Bu yazıda, bilişim teknolojilerindeki gelişmeler bünyesinde,kurumlann iç ve dış kaynaklı işçi-işveren düzenlemelerindeki durumu geleneksel istihdam düzenlemelerinden başlayarak yeni alternatif istihdam yapısı çeşitli boyutlarıyla ele alınıp dış kaynaklı istihdam sınıflandırması sunulmaktadır.

An Information technologies are developing very quickly in our time. Owing to these technological developments, organizations try to make new arrangements in employer-employee relationship. Lack of providing information concerning the advanced technologies and cost of integration to the new system, inefficient working of employees, working hours, legal details, social security and governmental politics are major problems. For these reasons, organizations have focused on varying forms of employment insourcing and outsourcing strategies. Most of the organizations, while using the key personnel providing information service partly from insourcing, prefer to use some of them from outsourcing. In this paper, we examine the situation of worker-organization relationship in insourcing and outsourcing arrangements from the sructural developments of view of information technologies and offer taxonomy of outsourcing employment that ranges from traditional employment, arrangement to new alternative employment insourcing and outsourcing strategies.
Effects of the Developments in the Information Sector on Insourcing and Outsourcing Employment Strategies